ANALISIS PREDIKSI KEPAILITAN PADA BANK UMUM SWASTA NASIONAL DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 – 2013 - Sumaniyatun Fadhilah; Indah Kurniawati (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2015)
The purpose of this study is to assess bankruptcy prediction in the National Private Banks Foreign Exchange listed in Indonesian Stock Exchange. This study uses the size of liquidity ratio of working capital to total assets. This study uses the find were the purposive sampling. The population in this study is the National Private Commercial Bank Foreign Exchange listed on the Indonesian Stock Exchange during the period of the study, namely between 2010 until 2013. The sample amounted to 21 banks during the 4 years that have been selected based on specific criteria. Based on the results of the analysis carried out stating that the National Private Commercial Bank Foreign Exchange listed in Indonesian Stock Exchange in 2010 there were 29 % of banks that are insolvent, 71 % of banks that are in the gray area, and no banks that are in not bankruptcy predictions. In 2011 29 % of banks that are insolvent, 67 % of banks that are in the gray area and 5 % are located on the banks not bankruptcy prediction. In 2012 29 % of banks that are insolvent, 67 % of banks that are in the gray area, and 5 % of banks that are in the prediction of the bank is not bankrup. In 2013 29 % of banks that are in bankruptcy prediction, 71 % of banks that are in the gray area, and there are no banks that are in not bankruptcy predictions. There is no difference in Z-score on bankruptcy prediction National Private Banks Foreign Exchange Listed in Indonesian Stock Exchange between 2010, 2011, 2012, and 2013.